1997
DOI: 10.1021/om970466z
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Lateral Stereocontrol Using the (π-Allyl)molybdenum System

Abstract: The preparation and reactions of several new (η3-allyl)molybdenum complexes are described. Functionalization of a carbon−carbon double bond adjacent to the π-allyl unit proceeds stereoselectively, and the stereochemical outcome of this reaction is discussed in light of the Curtin−Hammett principle. It is shown that carbonyl groups can also be functionalized with moderate stereoselectivity, and this behavior is rationalized on the basis of conformational analysis using molecular mechanics calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
0
10
1
Order By: Relevance
“…Overall, these results appear to be consistent with our earlier proposition that the methyl group at C(2) of the allyl ligand will favor the s-trans conformer to some degree, while a C(1) methyl substituent causes a more even distribution between s-trans and s-cis arrangements. However, the observed stereoselectivities for complex 10 are no better than those observed in our earlier work for the unsubstituted π-allyl complex 1 , presumably as a result of the low steric demand from the aldehyde oxygen versus the hydrogen. We anticipated that the situation would be very different for the alkene side chain in complexes 11 and 14 , as indicated from the NOE studies outlined above.…”
Section: Resultscontrasting
confidence: 75%
See 2 more Smart Citations
“…Overall, these results appear to be consistent with our earlier proposition that the methyl group at C(2) of the allyl ligand will favor the s-trans conformer to some degree, while a C(1) methyl substituent causes a more even distribution between s-trans and s-cis arrangements. However, the observed stereoselectivities for complex 10 are no better than those observed in our earlier work for the unsubstituted π-allyl complex 1 , presumably as a result of the low steric demand from the aldehyde oxygen versus the hydrogen. We anticipated that the situation would be very different for the alkene side chain in complexes 11 and 14 , as indicated from the NOE studies outlined above.…”
Section: Resultscontrasting
confidence: 75%
“…Within the last three years, our group has been successful in developing efficient synthetic routes toward a variety of new acyclic π-allylmolybdenum complexes, , in exploring the stereodirecting effect of molybdenum during functionalization, and in developing reliable methods of demetalation . In the present work, we have shown that functionalization of carbon−carbon double bonds and carbonyl groups adjacent to π-allylmolybdenum units is the result of the interplay between the directing effect of the metal and conformer populations, resulting in a 25:1 selectivity during double bond functionalization of complex 11 .…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Cationic molybdenum allyl nitrosyl complexes of the form [Mo(NO)(CO)(η 3 -allyl){HB(pz) 3 }] + are readily obtained via the reactions of allyl complexes [Mo(CO) 2 (η 3 -allyl){HB(pz) 3 }] with nitrosonium salts and have enjoyed considerable attention as intermediates in stoichiometric organic synthesis. , Accordingly, the reaction of the allyl complex [Mo(CO) 2 (η 3 -C 3 H 5 ){HB(mt) 3 }] ( 4 ) with [NO]BF 4 in 1,2-dimethoxyethane (−78 to 0 °C) was explored and found to provide the nitrosyl complex 3 (52%) rather than the anticipated salt [Mo(NO)(CO)(η 3 -C 3 H 5 ){HB(mt) 3 }]BF 4 . While this result was unexpected, it may be noted that nucleophilic (i.e., reductive) displacement of allyl ligands from molybdenum centers has precedent: e.g., the synthesis of [Mo(NCMe) 2 (CO) 2 (PPh 3 ) 2 ] from [MoCl(η 3 -C 3 H 5 )(NCMe) 2 (CO) 2 ] and PPh 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Murai et al recently reported that upon reaction of 1-(trimethylsilyloxy)-1,3-butadiene ( 4a ) with bis(acetonitrile)palladium dichloride (PdCl 2 (MeCN) 2 ), the η 3 -allylpalladium complex 5a was isolated as an 87:13 syn / anti mixture in almost quantitative yield (Scheme ). , In addition to this single example employing palladium, some related molybdenum and ruthenium complexes (e.g., 6a 11c and 6b ) have been isolated from similar reactions of 1-(trimethylsilyloxy)-1,3-butadienes with [(η 5 -C 5 Me 5 )(MeCN) 2 (CO)Mo] + BF 4 - or [Cp(MeCN) 2 (CO)Ru] + BF 4 - , respectively (Scheme ). Pearson et al recently reported the synthesis of an additional member of this family by a reduction−oxidation sequence (Scheme , Tp = hydridotris(1-pyrazolyl)borato) 4
5
…”
Section: Introductionmentioning
confidence: 99%